Sistem Pakar Diagnosa Penyakit Mata Pada Manusia Era Digital Berbasis Website - Prasetiyo, Bayu; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Eyes are a very important sense in human life to see. If the eye has an eye disorder or disease, it will be very fatal for human life. The development of technology in the digital era is very rapid so it cannot be denied, technology is one thing that is very closely related to humans today. The impact of technology on health, especially gadgets, can damage eye health. The screen of the gadget emits a light called high energy visible which is harmful to the eyes. because the eyes are too focused on the screen so that it causes an uncomfortable feeling. many people ignore the health conditions experienced and delays in handling due to lack of public knowledge of the types of eye diseases. then an expert system application program is made that can diagnose eye diseases in humans. This expert system application program was created to assist in finding conclusions about the eye disease suffered. The development of this application program uses the forward chaining inference method. This application program uses PHP programming, for the database using mySql, with this application you can find out the results of diagnosing eye diseases quickly and efficiently through the website.